Integration of Tropical Disease Screening in Reproductive Health Services at Amplas Community Health Center, North Sumatra - Irwandi Syahlis; Zaim Anshari; Mayang Sari Ayu; Marlina Elfa Lubis; Miftahul Mardiyah (PT Inovasi Pratama Internasional, 2026)
Tropical diseases remain important determinants of reproductive health in endemic regions; However, screening for these infections is rarely integrated into reproductive health services at the primary care level. This fragmentation contributes to low early detection and an increased risk of complications among women of reproductive age. This community service program aims to develop and implement an integrated model for tropical disease screening within reproductive health services at Puskesmas Amplas, Medan City. The program employed a pre–post intervention design involving women of reproductive age (15–49 years) selected through stratified random sampling. The intervention included clinical screening, health education, and the strengthening of referral and integrated recording systems. The results demonstrated a significant increase in early detection coverage and participants' knowledge, with a substantial proportion of respondents identified as having previously undetected risk factors for tropical diseases. Implementation of the integrated service model also enhanced the capacity of primary healthcare providers in delivering promotional and preventive services. These findings indicate that integrating tropical disease screening into reproductive health services is an effective and scalable approach to strengthening primary healthcare systems in endemic areas and improving community reproductive health outcomes